Marrow stimulation in football (soccer) players: a narrative review - Zachary D. Meeker; Nolan S. Horner; Kyle R. Wagner; Joshua T. Kaiser; Armaan F. Mazra; Brian J. Cole (Elsevier, 2022)
Introduction: The prevalence of focal cartilage defects in elite athletes is estimated to be as high as 36%, and treatment in professional football players poses a complex clinical challenge. Marrow stimulation is a common treatment option for athletes with symptomatic, contained, full-thickness chondral injuries. Objectives: To report the current indications for and efficacy of marrow stimulation in football players. Methods: PubMed, Scopus, and Embase were searched. All levels of evidence (I-IV) pertaining to marrow stimulation in football players were analyzed and presented in a narrative review. Results: Reported return to sport rates following microfracture range from 52% to 95%, with up to 67% of athletes returning to preinjury level of performance. Clinical outcomes improve shortly after microfracture but may decline by 2 years postoperatively. Augmented marrow stimulation techniques have since been developed in an effort to improve repair quality and clinical outcomes, though supporting data is limited. Conclusion: In professional football players, marrow stimulation is a viable treatment for the repair of small (<2 cm2), isolated cartilage injuries, though deterioration of mid- to long-term outcomes may hamper its widespread use. Multiple augmentation techniques have demonstrated the potential to generate a mechanically and biologically superior repair; however, more robust, high-level studies are needed to adequately assess efficacy.